Pengembangan Bahan Ajar Belajar dan Pembelajaran Berbasis Esperiental Learning - Anis Umi Khoirotunnisa; Sujiran Sujiran; Ali Noerudin (IKIP PGRI Bojonegoro, 2023)
Abstract: This study aims to further examine the development of teaching materials with the principle of experience-based learning or experiential learning in the Learning and Learning subject for students of the Mathematics Education Study Program at the IKIP PGRI Bojonegoro. The research method used is a literature study from several journals and proceedings related to experiential learning, both national and international journals from 2011-2021. The results of the study show that the experiential learning model is used to motivate students to understand material according to their learning style, some material presented in digital or conventional form can be made independently depending on the interests and learning experiences that have been obtained. Some of the teaching materials that are made by utilizing learning experiences include pop up books, interactive media based on Android and also graphic media. The selection of experiential learning models can trigger student creativity to create learning media independently. Abstrak: Penelitian ini bertujuan untuk meneliti lebih lanjut pengembangan bahan ajar dengan prinsip belajar berbasis pengalaman atau experiental learning pada matakulian Belajar dan Pembelajaran pada mahasiswa program studi pendidikan matematika IKIP PGRI Bojonegoro. Penelitian ini menerapkan metode dengan studi literatur dari beberapa jurnal maupun prosiding yang berkaitan dengan experiental learning baik jurnal nasional maupun internasional dari tahun 2011-2021. Hasil penelitian menunjukkan bahwa model experiental learning digunakan untuk memotivasi mahasiswa memahami materi sesuai dengan gaya belajarnya, beberapa materi yang disuguhkan dalam bentuk digital ataupun konvensional dapat dibuat secara mandiri tergantung dari minat dan pengalaman belajar yang telah didapatkan. Rencana pembuatan bahan ajar adalah dengan memanfaatkan pengalaman belajar diantaranya buku pop up, Interaktif media ajar dengan android dan juga media grafis. Pemilihan model experiental learning dapat memantik kreatifitas mahasiswa menciptakan media belajar secara mandiri.